PROTOTYPE SISTEM PENGENDALIAN PERANGKAT ELEKTRONIK BERBASIS IOT (INTERNET OF THINGS) MENGGUNAKAN VOICE CONTROL DAN BLYNK - Nur Afiyat; Mohamad Hariyadi; Muhammad Dimas Al Hakim (Jurnal RESISTOR (Rekayasa Sistem Komputer), 2021)
With the IoT based prototype electronic device control system, users can control electronic devices at home. Commands can be done in two ways, namely using voice or voice control with the Google Assistant application and using the interface buttons on the Blynk application. The prototype system can control electronic devices on and off and can control fan speed. The main component uses NodeMCU as a microcontroller that is equipped with a WiFi module so that it can be connected to the WiFi network needed to be connected to the internet. This system works when the user gives voice commands to control electronic devices via Google Assistant or the user can also control electronic devices by pressing a button on the Blynk application. Based on the results of testing the success of controlling using the voice control system has an average success of 100%, and testing the success of controlling using the Blynk system has an average of 100%. While the measurement of delay when controlling using voice control, each command has an average delay of 15.8797 - 17.9731 milliseconds, and while for testing using the interface button on the Blynk application, each command has an average delay of 15.8926-17. 5463 milliseconds.